2009
DOI: 10.3758/mc.37.4.447
|View full text |Cite
|
Sign up to set email alerts
|

The effects of "effort after meaning" on recall: Differences in within- and between-subjects designs

Abstract: What is the relationship between comprehension and memory? Ebbinghaus (1885Ebbinghaus ( /1964 began the scientific study of memory by attempting to avoid this question. By studying memory for three-letter trigrams under controlled experimental conditions, he assumed that he would not have to be concerned about the variability in how subjects understood or related to the stimuli. Nonetheless, Ebbinghaus noted that the lists of syllables he memorized exhibit very important and almost incomprehensible variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 59 publications
2
13
0
Order By: Relevance
“…was followed by a pause of a few seconds, versus no pause, before presenting the final word ("broom"). Interestingly, Zaromb and Roediger (2009) found that this effect only occurred in a within-subjects design in which, on a random half of trials, the disambiguating word was either embedded in the sentence or delayed by several seconds after presentation of the sentence. When participants were given only sentences in which the disambiguating word was either embedded or delayed, the delay was not beneficial.…”
Section: Discussionmentioning
confidence: 94%
“…was followed by a pause of a few seconds, versus no pause, before presenting the final word ("broom"). Interestingly, Zaromb and Roediger (2009) found that this effect only occurred in a within-subjects design in which, on a random half of trials, the disambiguating word was either embedded in the sentence or delayed by several seconds after presentation of the sentence. When participants were given only sentences in which the disambiguating word was either embedded or delayed, the delay was not beneficial.…”
Section: Discussionmentioning
confidence: 94%
“…On the basis of the idea that rehearsal of information consolidates memories for long‐term storage (Kandel, ), Hardiman (, ) posited that AI instruction improves retention by prompting students to rehearse content through the use of various visual and performing arts activities which may enhance student engagement (e.g., Smithrim & Upitis, ). Further, Rinne, Gregory, Yarmolinskaya, and Hardiman () argue that the arts may engage learners in thinking about new information in ways that improve retention, for example through semantic elaboration (e.g., Craik & Tulving, ), generation of information from a cue (e.g., Slamecka & Graf, ), enactment (e.g., Mohr, Engelkamp, & Zimmer, ), oral production (MacLeod, Gopie, Hourihan, Neary, & Ozubko, ), “effort after meaning” (e.g., Zaromb & Roediger, ), emotional arousal (e.g., Cahill & McGaugh, ), and pictorial representation (e.g., Paivio, ). The theory that arts integration improves retention of content is derived from the notion that the arts naturally take advantage of these strategies whereas conventional instruction typically does not.…”
Section: Arts Integration and Long‐term Retention Of Contentmentioning
confidence: 99%
“…More recently, however, Zaromb and Roediger (2009) have argued in a manner similar to McDaniel and Bugg (2008) that the memory advantage attributed to effort after meaning may instead arise for the same reason as the generation, enactment, and perhaps production effects—exerting unique effort to understand target material may be a relatively unusual occurrence, and this may lead to additional processing of information. One final note about effort after meaning is that, interestingly, Zaromb, Karpicke, and Roediger (2010) found that individuals have essentially no metacognitive awareness of any resulting gains in retention of information.…”
Section: Effort After Meaningmentioning
confidence: 99%